Keanekaragaman serangga pengunjung bunga pada tanaman tumpang sari kedelai dengan tanaman orok-orok (Crotalaria juncea) - Rahayu, Sayekti Kurnia; Supriyadi, Supriyadi; Supriyono, Supriyono; Wijayanti, Retno; Putri, Retno Bandriyati Arni (Perhimpunan Entomologi Indonesia, 2018)
Flowering plants can enhance the population of insect pollinators as well as crop yields. This study was aimed to determine the effect of intercropping between Crotalaria juncea and soybean on the diversity of flower-visiting insects and the role of wild pollinator to yield of soybean. The study was carried out on a single plot, with the treatment: without planting of C. juncea (control), planting of C. juncea surrounds of the soybean field, planting of C. juncea every 5 rows of soybean and planting of C. juncea every 10 rows of soybean. The effect of wild pollinator was identified by bagging the soybean by using insect net. The results revealed that planting of C juncea may increase the diversity of flower-visiting insect. The highest diversity index was 2.37 found on the plot with the planting of C. juncea every 10 rows of soybean. The highest diversity of flower-visiting insect was 18 species found in treatment by planting C. juncea every 5 rows of soybean. Flower-visting insects were dominated by Coccinella transversalis, Apis mellifera, Xylocopa virginica, Megachile parientina, Megachile relativa, Ropalidia fasciata, and Vespa sp. Wild pollinator by the open pollination (without bagging) may increase 30.11% number of pods, 44.63% number of seeds, and 15.44% seed weight per plant, this shows how important the role of wild/insect pollinators.